Environmental, Economic and Exergy Analysis of a Parabolic Trough Solar Collector with Finned Absorber Tube - Farhad Vahidinia; Alireza Aghaei; Hossein Khorasanizadeh (Journal of Heat and Mass Transfer Research)
Considering the excellent properties of hybrid nanofluids, it is a good idea to use them to improve the performance of solar collectors. The performance of a parabolic trough solar collector equipped with an internally finned absorber tube (IFAT) has been numerically studied based on the environmental, economic, exergy, and energy perspectives. The working fluid of the collector is hybrid nanofluid (HNF), consisting of of MWCNT and Fe3O4 nanoparticles and Therminol VP-1 as base fluid (BF). The volume fraction of nanoparticles is 3%, the operating fluid temperature is 600 K, and the Reynolds number is in the range of 2×104-2×105. The fluid flow is simulated using Ansys-Fluent software. Environmental analysis was done using the life cycle method, and economic analysis was based on the levelized cost of energy. Investigation of the results showed that the energy and exergy efficiencies of the collector when using the IFAT is higher than the smooth absorber tube (SAT), and using HNF is higher than base fluid. The maximum energy efficiency enhancement of the PTC using IFAT-BF, SAT-HNF, and IFAT-HNF compared to SAT-BF is 4.93, 1.49, and 5.35%, respectively, and the maximum exergy efficiency enhancement is 6.09, 1.6 and 6.6%, respectively. Based on the economic approach, it was observed that for the Re lower than 5×104, the use of PTC with IFAT is more economical than the PTC with SAT. The environmental analysis showed that the use of the PTC with SAT compared to PTC with IFAT and also the use of HNF instead of the BF produces less CO2 in the life cycle of the collector.